Traditional uses, botanical description, phytochemistry, and pharmacological activities of Phytolacca acinosa: a review - Tooba Khalid; Chieh-Wei Chang; Samir Anis Ross; Faiza Naseer; Abdul Qadeer; Chien-Chin Chen; Chien-Chin Chen; Chien-Chin Chen; Chien-Chin Chen; Hafiz Abdul Rafey (Frontiers in Pharmacology)
BackgroundPhytolacca acinosa is an herbaceous herb belonging to the Phytolaccaceae family. The plant has a long history of usage in traditional medicine for treating a variety of ailments including infectious diseases, edema, inflammation, gastric, and abdominal distress. The traditional use, phytochemistry, and pharmacological properties of Phytolacca acinosa are outlined in this article.Main textTo date, few bioactive molecules have been identified and isolated from the plant, such as phytolacacinoside A, esculentoside H, jaligonic acid and esculentoside B, phytolaccanol and epiacetyl aleuritolic acid, esculentoside A, esculentoside C, esculentoside D, esculentoside T, esculentoside S, sitosterol. The literature related some of the reported ethnomedicinal uses of the plant to these compounds found in different parts of the plant.ConclusionThe in-depth knowledge about the significance of Phytolacca acinosa presented in this review may open up opportunities for research development in drug discovery and a better comprehension of the therapeutic advantages of the plant.